Participants’ satisfaction with social security is closely associated with their acceptance of vulnerable groups: a nationwide cross-sectional study in China - Guo, Chaowei; Wu, Yifan; Ge, Lina; Qi, Li; Ma, Yi; Zang, Shuang (Frontiers in Psychology, 2025)
IntroductionSocial security, as a core component of the national welfare system, has consistently played a crucial role in ensuring the basic livelihood of citizens and promoting social equity and justice. Against this backdrop, this study explores the association between social security satisfaction and acceptance of vulnerable groups.MethodsThis study involved 9923 participants. Generalized linear regression and smooth curve fitting were used to assess the association between social security satisfaction and acceptance of vulnerable groups. Threshold effect was examined by piecewise regression. We conducted subgroup analyses and assessed the potential interaction effect.ResultsA non‑linear association was detected between social security satisfaction and inclusion of vulnerable groups with an inflection point of 45.00. When social security satisfaction was < 45.00, inclusion of vulnerable groups increased with increasing social security satisfaction score up to inflection point. The association between social security satisfaction and inclusion of vulnerable groups differed across gender, education level, and spouse subgroups.DiscussionThe study reveals the importance of social security satisfaction on their acceptance of vulnerable groups. It has a significant meaning in enhancing individuals’ acceptance of vulnerable groups level.